PEMBERIAN PILATES EXERCISE TERHADAP PENURUNAN NYERI HAID - Ayu Andera, Neta (Stikes Yarsi Mataram, 2024)
Dysmenorrhea is a disruption in menstrual blood flow/menstrual pain. If dysmenorrhea pain is not treated immediately, it will affect the individual's mental and physical function so that non-pharmacological measures are needed. Non-pharmacological therapy that can be done is Pilates exercise.. The aim of providing pilates exercise is to reduce menstrual pain at SMPN 7 Kota Kediri. Method of providing pilates exercise counseling to reduce menstrual pain to 15 female students at SMPN 7 Kota Kediri. The results of counseling on providing pilates exercise to reduce menstrual pain in teenagers at SMPN 7 Kota Kediri, can apply pilates exercise to reduce dysmenorrhea pain which does not cause side effects in reducing the incidence of dysmenorrhea pain.Conclusion Giving pilates exercuse can reduce menstrual pain in adolescents at SMPN 7 Kota Kediri, so adolescents are advised to apply pilates exercise to reduce dysminorea pain that does not cause side effects in reducing dysminorea pain